Budaya Pangan Masyarakat Badui Berbasis Kearifan Lokal (Study Budaya Pangan Badui Luar) - Mohammad Syaltut Abduh Syaltut; Nurbaeti Nurbaeti; Jajang Gunawijaya (JURNAL GASTRONOMI INDONESIA, 2023)
The food culture of the Badui people is extremely diverse and still upholds the traditional knowledge that has been passed down through the generations. The goal of this study was to learn about the Badui community's food customs, namely how to procure, prepare, serve, eat, and preserve food so that it might be developed as a vehicle for importation. This kind of research uses a naturalistic/ethnographic paradigm and is qualitative. Observation, a review of the literature, in-depth interviews, and researchers themselves as the main tool were used as data gathering techniques. Interviews with informants Jaro Saija (village chief/Jaro Pamarentah), Mr. Sukma (a resident of outer Badui), and Mr. Sudirman serve as the primary sources of data (PHRI Banten). The existence of leuit as a rice barn and the custom of huma and ngaseuk rice each time they plant rice or secondary crops demonstrate that the Outer Badui community still upholds its food culture. Food ingredients can sometimes be prepared via frying, boiling, and roasting. The cooking equipment are still conventional, but some of the serving items are contemporary. The Badui continue to eat natural foods, but they also purchase other essentials outside of their area.